Fatigue Flexural Performance of Short-Span Reinforced Concrete T-Beams Considering Overloading Effect - Chenxu Zhuang; Jinquan Zhang; Ruinian Jiang (The Baltic Journal of Road and Bridge Engineering)
Traffic volume increase and higher proportion of heavier trucks have raised the potential risk of fatigue failure of short-span reinforced concrete beams. To investigate the fatigue behavior of short-span reinforced concrete beams with and without the overload effect, nine 5 m reinforced concrete T-beams were cast and tested. Two beams were tested under static loading to determine the ultimate strength; the remaining seven beams were subjected to cyclic loading with constant-amplitude load ranges. In addition, two of the seven beams were subjected to instant overloading. It was observed that the typical failure mode under cyclic loading was the fatigue fracture of tensile reinforcing bars. The introduction of instant overloading resulted in a remarkable reduction of fatigue life. Among all the parameters, the stress range of the reinforcing bars showed the highest effect on the fatigue life. In the end, the fatigue safety provisions in the current reinforced concrete beam design codes were evaluated based on the fatigue limits and S-N curves.